Uso de coentro e sorgo granífero em cultivo de tomate orgânico visando ao aumento de insetos predadores e polinizadores - Santos, Laís da Conceição dos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The objective of this study was to evaluate the effects of the strategy "push-pull" using sorghum plants (Sorghum bicolor L.) and coriander (Coriandrum sativum L.) on pests insect and predators and evaluate the abundance and species richness of Coleoptera, Hemiptera and bees in organic tomato. The experiment consisted of two treatments: a) polyculture; b) tomato monoculture. The polyculture was formed by tomato plants, Solanum lycopersicum L., coriander and sorghum. The evaluations were carried out fortnightly, from planting to end of crop cycle. In each plot the insects were sampled visually examining the whole plant, considering randomly 10 tomato plants, 10 plants of C. sativum and 10 plants of S. bicolor. The design was a randomized block with split plot in the time (Split-Plot) with 12 repetitions, the main treatments (plots) were represented by mono and tomato polyculture and secondary treatments (subplots) represented by the collection dates, having been evaluated eight dates in each crop cycle. The presence of sorghum and coriander did not significantly reduce the population density of Tuta absoluta (Meirick) (Lepidoptera: Gelechiidae), Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), Caliothrips phaseoli Hood (Thysanoptera: Thripidae) and Aphis gossypii Glover (Hemiptera: Aphididade) in tomato in greenhouse. The tomato-coriander-sorghum polyculture favors the occurrence of insect predators, especially after flowering coriander. Coriander provides greater diversity of insect predators, especially Franklinothrips vespiformis (Crawford) (Thysanoptera: Aeolothripidae). Coriander has no repellent effect on phytophagous Coleoptera and Hemiptera in organic tomato cultivation. The plant diversification promotes increase in the abundance and species richness of beetles and hemipteran in organic tomato. The combination of coriander and tomato plants in greenhouse helps to attract pollinating insects.

O objetivo do presente estudo foi avaliar os efeitos da estratégia “pushpull” utilizando plantas de sorgo (Sorghum bicolor L.) e coentro (Coriandrum sativum L.) sobre insetos-praga e predadores e avaliar a abundância e riqueza de espécies de Coleoptera, Hemiptera e abelhas, em tomateiro orgânico cultivado em casa-devegetação. O experimento foi composto de dois tratamentos: a) policultivo e b) monocultivo de tomateiro. O policulivo compreendeu plantas de tomate, Solanum lycopersicum L., de coentro e sorgo. As avaliações foram quinzenais e realizadas desde o plantio até o fim do ciclo da cultura. Em cada parcela os insetos foram amostrados visualmente examinando-se toda a planta, considerando-se aleatoriamente 10 plantas de tomateiro, 10 plantas de C. sativum e 10 plantas de S. bicolor. O delineamento utilizado foi o de blocos casualizados com parcelas subdivididas no tempo (Split-Plot), com 12 repetições, sendo os tratamentos principais (parcelas) representados pelo mono e policultivo de tomateiro e os tratamentos secundários (subparcelas) representados pelas datas de coleta, sendo oito datas de coleta para cada safra. A presença de sorgo e coentro não reduz significativamente a densidade populacional de Tuta absoluta (Meirick) (Lepidoptera: Gelechiidae), Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), Caliothrips phaseoli Hood (Thysanoptera: Thripidae) e Aphis gossypii Glover (Hemiptera: Aphididade) no tomateiro em casa-de-vegetação. O policultivo tomateiro-coentrosorgo favorece a ocorrência de insetos predadores, sobretudo após a floração do coentro, que proporciona a ocorrência de Franklinothrips vespiformis (Crawford) (Thysanoptera: Aeolothripidae). O coentro não possui efeito repelente sobre coleópteros e hemípteros fitófagos. A associação do coentro com o tomateiro em casa-de-vegetação contribui para a atração de insetos polinizadores. A diversificação vegetal promove aumento na abundância e riqueza de espécies de besouros e percevejos em tomateiro orgânico.
Coriander and sorghum use aiming to increase insect predators and pollinators in organic tomato
Keywords: Controle biológico conservativo; Inimigos naturais; Push pull; Solanaceae; Entomologia; Conservative biological control; Natural enemies; Entomology